Urban Sustainability Index of Guwahati City - Borah, Bhaskar; Borah, Chayanika (The journal of contemporary issues in business and government, 2021)
In the past century the process of urbanisation over the globe reaches at its peak. Urbanisation brings changes to the fabric of socio economic structures of cities. Cities are the main hubs of economic activities and are being urbanized rapidly. But the question arises here to what extent urban growth pattern in a certain city is sustainable. The idea of ’sustainable development’ of cities was addressed in Agenda 21 of Earth Summit which aims at providing city planning strategies to achieve sustainability in development pattern. In 1986 Indian Prime Minister Rajiv Gandhi constituted the National Commission on Urbanisation which was followed by passage of 74 th Constitution Amendment Act (CAA) in 1992. Guwahati is one of the fastest growing city of North East Region of India. Guwahati is experiencing steep rise in population in the past few decades. It also possess potentials of connecting the Southeast and South Asian Nations which brings into notice the importance of its development which must be sustainable in nature for the decades to come. The main aim of this study is to develop Urban Sustainability Index (USI) of Guwahati city. Through USI we will check the state of sustainability in urban growth pattern of the city .USI is measured in quantitative unit taking the relevant information on three indicators viz. economic, environmental and social .Comparing the information with best and poor threshold values of most and poor sustainable regions of the world (London and Shanghai respectively) we will get the relative indicators. Finally a composite indicator will give us the value of USI. The value of USI will be lying between the range of 0 to 1 indicating 1 is best and 0 is worse sustainable condition.